Video-Based Pairwise Comparison: Enabling the Development of Automated Rating of Motor Dysfunction in Multiple Sclerosis - , Jessica Burggraaff; , Jonas Dorn; , Marcus D'Souza; Morrison, Cecily; , Christian P. Kamm; , Peter Kontschieder; , Prejaas Tewarie; , Saskia Steinheimer; Sellen, Abigail; , Frank Dahlke; , Ludwig Kappos; , Bernard Uitdehaag (Archives of Physical Medicine and Rehabilitation, 2020)
To examine the feasibility, reliability, granularity, and convergent validity of a video-based pairwise comparison technique that uses algorithmic support to enable automated rating of motor dysfunction in patients with multiple sclerosis (MS).